Light‐emitting diode therapy induces analgesia and decreases spinal cord and sciatic nerve tumour necrosis factor‐α levels after sciatic nerve crush in mice. (21st January 2013) - Cidral‐Filho, F.J.; Martins, D.F.; Moré, A.O.O.; Mazzardo‐Martins, L.; Silva, M.D.; Cargnin‐Ferreira, E.; Santos, A.R.S.
Abstract: Background: Neuropathic pain is severely debilitating and resistant to pharmacological approaches; therefore, the study of therapies to complement its treatment is especially relevant. In a case report study, light‐emitting diode therapy (LEDT) has shown analgesic activity as well as reduced the expression of pro‐inflammatory cytokines in a rabbit osteoarthritis model and in calcaneal tendinitis in rats. Although LEDT stimulated morphofunctional recovery after nerve injury in rats, its effect against neuropathic pain has not been tested. Methods: To that purpose, mice under anaesthesia were subjected to the sciatic nerve crush (SNC) model. On the seventh post‐operative day, after determining analgesic dose (energy density in joules), LEDT (950 nm, 80 mW/cm 2, 2.5 J/cm 2 ) was irradiated, daily for a period of 15 days, on the skin over the crush site. Results: Compared with the SNC group, LEDT reduced mechanical hypersensitivity but not cold hypersensitivity which is induced by SNC, decreased spinal cord and sciatic nerve levels of tumour necrosis factor alpha (TNF‐α) but did not alter interleukin (IL)‐1β and IL‐10 levels, and finally, failed to accelerate motor functional recovery and morphological nerve regeneration. Conclusion: Taken together, these data provide first‐hand evidence of LEDT effectiveness against neuropathic pain induced by SNC, with corresponding decrease of pro‐inflammatory cytokine levels, both in the sciatic nerve and in the spinal cord, although at a small analgesic dose, LEDT failed to accelerate nerve regeneration.